2002
DOI: 10.1038/nature00893
|View full text |Cite
|
Sign up to set email alerts
|

Self-regeneration of a Pd-perovskite catalyst for automotive emissions control

Abstract: Catalytic converters are widely used to reduce the amounts of nitrogen oxides, carbon monoxide and unburned hydrocarbons in automotive emissions. The catalysts are finely divided precious-metal particles dispersed on a solid support. During vehicle use, the converter is exposed to heat, which causes the metal particles to agglomerate and grow, and their overall surface area to decrease. As a result, catalyst activity deteriorates. The problem has been exacerbated in recent years by the trend to install catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
906
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,065 publications
(951 citation statements)
references
References 10 publications
17
906
0
3
Order By: Relevance
“…Changing the reaction atmosphere has also been exploited for improving the catalyst lifetime: In so‐called “intelligent catalysts”, the oxidation of Pd nanoparticles was used to incorporate Pd into a perovskite lattice (e.g. Pd and LaFeO 3 to LaFe 0.95 Pd 0.05 O 3 ) 36, 37. Under reducing conditions Pd moves back to the surface inducing a self‐regeneration of the catalyst since the metal particles are effectively redispersed on the surface.…”
Section: Dynamic Reaction Conditions From a Catalysis Point Of Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…Changing the reaction atmosphere has also been exploited for improving the catalyst lifetime: In so‐called “intelligent catalysts”, the oxidation of Pd nanoparticles was used to incorporate Pd into a perovskite lattice (e.g. Pd and LaFeO 3 to LaFe 0.95 Pd 0.05 O 3 ) 36, 37. Under reducing conditions Pd moves back to the surface inducing a self‐regeneration of the catalyst since the metal particles are effectively redispersed on the surface.…”
Section: Dynamic Reaction Conditions From a Catalysis Point Of Viewmentioning
confidence: 99%
“…Sintering (Figure 4 b) describes the agglomeration and gradual growth of nanoparticles. Usually this is connected to a decrease of the catalytic activity of the catalyst which is a common problem in heterogeneous catalysis,13, 36, 37, 44 as well as in electrocatalysis 16. Systems composed of several components often feature strong metal–support interactions.…”
Section: Snapshots On Working Catalysts: Case Studies Unravelling Stmentioning
confidence: 99%
“…1) 5) Orthorhombic REFeO 3 (o-REFeO 3 ) with the perovskite structure has recently received much attention in the catalyst field. For example, Nishihata et al 6) reported that LaFe 0.57 Co 0.38 Pd 0.05 O 3 with the perovskite structure is successfully applied as a catalyst for the vehicle exhaust treatment. Andrews et al reported that LaFe 0.95 Pd 0.05 O 3 is an effective catalyst for Suzuki Miyaura coupling reaction in organic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Partial substitution of B-site ions with other ions is expected to modify the perovskite structure and thus improve the catalytic performance. A typical example is that doping very small amounts of Pd to LaFeCoO 3 and LaFeO 3 can dramatically promote the catalytic durability in vehicle exhaust abatement [4,6]. LaFe 0.57 Co 0.38 Pd 0.05 O 3 , even after long-term ageing at 1173 K, still displayed superior activity and stability to a Pd/Al 2 O 3 catalyst [6].…”
Section: Introductionmentioning
confidence: 99%
“…A typical example is that doping very small amounts of Pd to LaFeCoO 3 and LaFeO 3 can dramatically promote the catalytic durability in vehicle exhaust abatement [4,6]. LaFe 0.57 Co 0.38 Pd 0.05 O 3 , even after long-term ageing at 1173 K, still displayed superior activity and stability to a Pd/Al 2 O 3 catalyst [6]. The Pd species, in response to the inherent redox fluctuations in the automobile exhausts, reversibly and rapidly incorporated into and moved out of the perovskite lattice and thereby the sintering of Pd grains could be suppressed [4,6−8].…”
Section: Introductionmentioning
confidence: 99%